Functional Brain Connectivity and Cognition: Effects of Adult Age and Task Demands - Chou, Ying-hui (2013)
Previous neuroimaging research has documented that patterns of intrinsic (resting-state) functional connectivity (FC) among brain regions covary with individual measures of cognitive performance. Here, we examined the relation between intrinsic FC and a reaction time (RT) measure of performance, as a function of both age group and task demands. We obtained filtered, event-related functional magnetic resonance imaging (fMRI) data, and RT measures of visual search performance, from 21 younger adults (19–29 years) and 21 healthy, older adults (60–87 years). Age-related decline occurred in the connectivity strength in multiple brain regions, consistent with previous findings. Among eight pairs of regions, across somatomotor, orbitofrontal, and subcortical networks, increasing FC was associated with faster responding (lower RT). Relative to younger adults, older adults exhibited a lower strength of this RT-connectivity relation and greater disruption of this relation by a salient but irrelevant display item (color singleton distractor). Age-related differences in the covariation of intrinsic FC and cognitive performance vary as a function of task demands.